ANALISIS KETERKAITAN SEKTOR PERTANIAN, DAMPAK PENYEBARAN DAN DAMPAK PENGGANDA, SERTA DAMPAK PERMINTAAN AKHIR DALAM PEREKONOMIAN DI KABUPATEN TASIKMALAYA - R.Sana Aulia Salsabila; Trisna Insan Noor; Tuti Karyani (Universitas Galuh, 2022)
Tasikmalaya Regency has an agricultural sector which plays a fairly high role in the regional economy. The area of paddy fields is the area that dominates other garden sectors. Therefore, the objectives to be achieved in this study are to analyze the linkages of the agricultural sector, the impact of the spread and the impact of the multiplier, as well as the impact of final demand on the economy in Tasikmalaya Regency. The research method used in this research is descriptive quantitative method. The data used is secondary data, namely input-output table data in Tasikmalaya Regency in 2020. While the analysis used is input-output analysis. The results of this study indicate that the agricultural sector has an important role for the economy in Tasikmalaya Regency when viewed from the structure of the economy. Based on the input-output analysis, the value of the linkage, the impact of the spread and the impact of the multiplier obtained by the agricultural sector has a high value. The agricultural sector has the ability to increase the growth of other sectors, both upstream and downstream. while based on the leading sector, the agricultural sector is the second priority after the wholesale and retail trade sector.